Income distributional effects of using market-based instruments for managing common property resources - Msangi, Siwa; Howitt, Richard E. (Wiley, 2007)
In this article, the authors show the trade‐offs between efficiency and equity that arise from the application of market‐based instruments to a heterogenous population of agents drawing from a natural resource pool. Using the example of groundwater, they find that there are overall losses in allocative efficiency when the centralized planner is constrained by equity considerations, and that the distribution of gains or losses to management becomes skewed asymmetrically across agents. These results demonstrate the importance of considering both efficiency gains and disparities in distributional inequity, when designing policy instruments that create winners and losers with potentially serious sociopolitical ramifications.